PWWP3A disrupts the assembly of VISA/MAVS signalosome to inhibit innate immune response against RNA viruses - Mengling Shi; Cong Wang; Zhen Chen; Yidan Zhou; Liang Yue; Yu Liu; Tiannan Guo; Jun Shang; Haotian Xu; Yu Zhang; Mengcheng Luo; Caoqi Lei (Nature Communications)
Abstract VISA/MAVS is crucial in antiviral innate immunity. Upon RNA virus infection, VISA recruits TBK1 via TRAFs to mitochondria, inducing IRF3 phosphorylation and type I interferons. However, TBK1 recruitment mechanisms via individual TRAFs are unclear. Here, we reveal that PWWP domain-containing 3A (PWWP3A) serves as a negative regulator of RNA virus-triggered signaling. During viral infection, PWWP3A translocates from nucleus to the mitochondria, competing with TRAF6 for binding to VISA, thereby impeding the recruitment of TBK1 and inhibiting IRF3 activation. However, the extent of PWWP3A-mediated inhibition is regulated by the E3 ligase PJA2, which induces PWWP3A degradation post-infection, highlighting the intricate regulatory network in antiviral immunity. Consistently, PWWP3A deficiency enhances antiviral responses, and Pwwp3a −/− mice exhibit elevated levels of type I interferons and displayed greater resistance following RNA virus infection. Together, our findings unveil the inhibitory role of PWWP3A in virus-triggered signaling, which provides insights into preventing excessive immune responses.